THE ROLE OF HUMAN DEVELOPMENT INDEX, INVESTMENT, GOVERNMENT EXPENDITURE IN ECONOMIC GROWTH - Wisnu Satria; Mirzatul Kadri; Muhammad Syahrul Mubarak (Universitas Tidar, 2025)
The purpose of this study is to evaluate the role of the Human Development Index (HDI), investment, and government spending on economic growth in Paser Regency from 2009 to 2020. The data used is derived from annual secondary data and analyzed using path analysis with AMOS 23 to examine direct and indirect relationships, with unemployment as a mediating variable. The results show that investment, particularly through increased production capacity and economic activity, has a positive and significant effect on economic growth, while government spending and HDI have a negative effect on growth. This indicates that regional budget allocation is still dominated by unproductive spending, while the increase in HDI is not yet in line with labor market needs. Furthermore, mediation analysis shows that unemployment does not play a significant role in channeling the influence of independent variables on growth. Therefore, Paser's economic dynamics are more influenced by structural elements than by labor market cycles. At the district level, this study provides empirical benefits by highlighting issues of fiscal inefficiency, human resource mismatches, and dependence on the mining sector. One consequence of this policy is that government spending must be allocated to more productive sectors, investment must be more diversified outside the extractive sector, and human resource development programs must be tailored to the needs of the labor market. It is hoped that these measures will boost sustainable economic growth and reduce structural vulnerability.